Pediatric skull bone defect due to epidermoid cyst - Sinurat, Robert; Gultom, Fajar Lamhot (Universa Medicina, 2021)
BackgroundTumors of the skull usually affect adult patients and less than twenty percent of pediatric patients. As the tumors grow, the surrounding bone may undergo destruction and erosion. When the tumors are located in the fontanel, the timely closure of the fontanel may be inhibited. Epidermoid cysts are benign tumors that are intracranially located and very rarely in the midline of the cranium. Meanwhile about 32% of stratified-squamous epithelial epidermoid cysts affect the head and neck region and only 6.7% occur in the scalp. We report an unusual epidermoid cyst located and growing in the anterior fontanel of a pediatric patient and inhibiting fontanel closure.Case Description A 21-month-old boy and his parents visited our polyclinic because there was a lump on his anterior fontanel since four months before they came to the hospital. The lump was initially the size of a peanut and had grown to become as large as a quail’s egg. The physical examination was normal and the brain CT-scan showed bone destruction without any intracranial lesion. The tumor was excised on the preoperative diagnosis of dermoid cyst. Histopathology examination showed the characteristics of an epidermoid cyst. The cyst had a wall and was full of keratin flakes without hair follicles or sebaceous glands. Follow-up one year after complete excision did not reveal any recurrence. ConclusionEpidermoid cysts in the skull of pediatric patients must be completely excised as soon as possible because their growth can damage the bone and inhibit the closure of the sutures.